(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Corneal ulcer is a medical condition that is the most significant cause of morbidity and blindness worldwide, caused most often by bacteria and fungi. This study aimed to determine the microbiological profile of the causes of corneal ulcers at Sultan Agung Islamic Teaching Hospital, Semarang. Methods: This research is a descriptive study with a cross-sectional design. Samples were all patients with corneal ulcers at Sultan Agung Islamic Teaching Hospital Semarang from July 1, 2018 – July 31, 2023; the sampling method used consecutive sampling, and the sample size was the total population. Samples were taken using a scraping on the cornea, then implanted directly in Blood Agar Plate and Saboroud Dextrose Agar. Bacterial colonies are identified using API®, and a susceptibility test was performed on Muller Hinton Agar using the Kirby Bauer method. Fungal colonies are identified using Lacto Phenol Cotton Blue, Gram, and Germ Tube. Results: There were 85 samples, with no growth as many as 41 samples (48%). Fungi cause more infections than bacteria. The fungus that causes the most extensive corneal ulcers is Aspergillus sp as much as 13, while the group of bacteria is Staphylococcus coagulase negative as much as 4 (50%) Conclusion: Most of the microorganisms that cause corneal ulcers are fungi compared to bacteria. No Multi-Drug Resistant Organisms were found in the causative bacteria, and no azole resistance was found in fungi. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 676-681